From prophecy to apocalypse: the verb tenses of Jerusalem in Robert the Monk's Historia of the First Crusade. Issue 3 (26th May 2016) - Gabriele, Matthew
ABSTRACT: In the prologue to his Historia of the First Crusade, Robert the Monk posed this rhetorical question: 'since the creation of the world what more miraculous undertaking has there been (other than the mystery of the redeeming Cross) than what was achieved in our own time by the journey of our own people to Jerusalem?' For Robert, the answer was of course simple: nothing was more miraculous. Yet when we answer that question along with Robert, we lose sight of its significance, and how staggering that claim actually would have been in the early twelfth century. For Robert, the events of 1095–9 signalled a new moment in sacred history. Old Testament prophecy had come true in his own day. What 'was to come' became what simply 'was'. For Robert the Monk, prophecy became apocalypse.